(3CNdGbjGJ hfeGPL GdSdhc GdTQGFj ddeSJgdc GdUfGYj (B/s - (3Hf KGeQ, cdKhes ((3GdLRGFQ(B: s (3OGQ GdHGMK ddfTQ hGdETgGQ(B, s, 2023)
(3GdeSJgdc GdUfGYj hSdhcg GdGSJgdGcj, ehba eQcR GJNGP GdbQGQ ef hVYjGJ GdTQGA, eQGMd YedjI GdTQGA hGdfeGPL GdeaSQI dgG, cPdc GdYhGed GdeDKQI Ydi eQcR GdTQGA hGNJjGQ GdehQOjf, hGdSdhc GdTQGFj GdOhdj, hCNjQG GdeYVdGJ GdCNdGbjI aj GdShb GdUfGYjI(B.s
(3eQGLY U(B.161s
Keywords: (3GdSdhcs; (3GdeSJgdchfs